Variation of Mechanical Properties and Temperature Control in Hot Asphalt Mixtures Through the Incorporation of Glass Powder, Province of Huancayo - Riveros Llacua, Cleder Cristhian (2024)
Asphalt is a material composed of a mixture of various hydrocarbons of natural origin. In Peru, almost all of the paved roads are made of hot asphalt mixtures, some of which are constructed at altitudes exceeding 3000 meters above sea level (m.a.s.l.). However, maintaining the mixture temperature at the optimal level for placement and compaction is challenging. The difficulty in temperature control arises from the location of the asphalt plant, often due to a lack of aggregates that are situated far from the area where the asphalt mixture is to be placed. This study underscores the significance of improving the mechanical properties and extending the temperature sustainability of hot asphalt mixtures by incorporating glass powder-modified asphalt bitumen—a topic with limited literature in Peru. Tests were conducted on 93 Marshall specimens and 5 viscosity control points, divided into two groups: one for conventional asphalt mix and another for glass powder-modified mix. The results revealed substantial enhancements in stability, flow, and Lottman tensile strength when 3% of glass was added to the asphalt bitumen, along with a reduction in mixture temperature when 2% of glass was incorporated, resulting in a cooling effect during the addition of glass. In conclusion, glass-modified asphalt mix demonstrated a positive influence on its mechanical properties and the cooling process, making it a more effective choice for field applications.